OPEN UNIVERSITY AND DISTANT LEARNING: A PANACEA TO ENHANCED ACCESS TO HIGHER EDUCATION IN NIGERIA - Okafor Kalu, Mabel; Judith Ngwakwe, Ezinne (African Journal of Social and Behavioural Sciences, 2024)
pen and distance education has offered access to educational opportunities on the basis of where they live or work, poor economic circumstances, and social status. It was low access to higher education in the country that necessitated the establishment of Open University in 1983 to ensure equity and equality of opportunities and wider access to education, with a view to mopping all those who need higher education but are left out by the conventional education system. Open and distance learning is important because it makes education accessible and reduces costs while maintaining quality. This paper therefore stresses the use of open and distance learning as an avenue to attain knowledge and education that would put all Nigerian individuals who were denied access to conventional universities in a better path toward achieving their desired aspirations in life.